Association of Self-Perceived Psychological Stress with the Periodontal Health of Socially Deprived Women in Shelter Homes - A. Tanveer, Syeda (Int J Environ Res Public Health, 2021)
The present study aimed to assess the effect of self-perceived psychological stress on the periodontal health of socially deprived women. The study included three hundred and eighty-five socially deprived women residing in shelter homes. The presence of stress and its severity was assessed by using Sheldon Cohen’s 10-item perceived stress scale (PSS), and periodontal health status was assessed utilizing the community periodontal index. Statistical analyses were performed using an independent sample t-test, a one-way ANOVA, the Pearson chi-Square test, and binary logistic regression. Results: A total of 385 samples were included, the majority of whom (n = 297; 72.5%) belonged to the age group of 15–30 years. There were 34 (8.8%) participants who were educated up to graduate level. A total of 47.8% of the women were found with healthy periodontal status, and 52.5% of the samples were diagnosed with major psychological stress. Half of the samples (201-52.2%) had a periodontal problem. The mean PSS was found statistically significant concerning age group, education, and psychological stress level. In the univariate logistic regression analysis, a significant association of periodontal status was observed with the age group 31–45 years [(OR = 1.76; 95% C.I (1.11–2.78)] and with a major psychological stress level [(OR = 2.60; 95% C.I (1.72–3.93)]. Psychosocial stress among socially deprived women was found to be a risk factor for periodontal disease.